La localización de webs dinámicas: objetos, métodos, presente y futuro - Jesús Torres-del-Rey; Emilio Rodríguez-V.-de-Aldana (JoSTrans: The Journal of Specialised Translation)
Over the last decade, dynamic websites (which are structurally much more complex than traditional static websites, with localisable content scattered in many more files and databases) have grown exponentially, mainly due to specialised Web Content Management Systems (WCMS), which help create and maintain websites with little or no knowledge of the underlying technology and computer languages. This paradigm shift has taken place just as Computer-Aided Translation Tools have become more and more effective and usable for the translation and localisation of static websites. As a consequence, we seem to be missing out on recently acquired advantages such as visual and functional contextualisation, the ability of web re-creation for immediate publication, and translation memory and terminology aids. This research aims, from a didactic perspective, at exploring the state of the art of static and dynamic web localisation by comparing their translation objects and methods, and analysing the place of the translator/localiser in this process. We then suggest possible avenues for research and development in order to regain lost ground with the spread of new website WCMSs, including the use of standards such as XLIFF, ITS and other semantic web technologies.